Kompresi Gambar dengan Transformasi Wavelet - Dessy Kusumaningrum (MATHunesa: Jurnal Ilmiah Matematika, 2020)
Current technological developments have increased quite rapidly, one of which is in digital image processing. The use of digital images sometimes experience problems during the upload process or when users want to insert image files on a platform but are limited by the maximum image file size. The image file to be uploaded must go through a digital image processing so that the image file size can match the requested maximum limit. One technique that can be used in this problem is compression. Compression is one of the main techniques of image processing. Large image size results in reduced data or memory storage. So that compression is also carried out to reduce the use of data storage and hence communication costs. There are many methods used in image compression today. One method used is to use wavelet transforms. In this research, the mother wavelet used is the Biorthogonal wavelet. The purpose of this study is to find out how much the accuracy of the Biorthogonal wavelet to be implemented in color images and to determine the image quality and performance of the Biorthogonal wavelet function in image compression. Decomposition levels used in this study are level 1, level 2, and level 3. The results of the study are displayed in the form of images before compression and image compression results, equipped with PSNR, MSE values, compression ratio, and the size of the compressed images.